Penanda jamak dalam bahasa Prancis dan bahasa indonesia. - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
ABSTRAK The pluralities of French can be found in both writing and oral. In writing, there are the additions of âx and âs, or the others variations which depend on the rules of nouns and adjectives. There are the concordances between nouns and adjectives or subjects and predicates in past tense, passive voice, and complete sentence with que. On the other hand, in oral, there are the pronunciations of the articles of nouns and liaison. The pluralities in Indonesian are in repetitions of nouns, verbs, adjectives, the numeral, and the adjectives that have plural meaning.